2017
DOI: 10.1016/j.matdes.2017.04.019
|View full text |Cite
|
Sign up to set email alerts
|

Urchin-inspired ZnO-TiO2 core-shell as building blocks for dye sensitized solar cells

Abstract: We applied the core-shell concept to an urchin-inspired ZnO nanowire photoanode building block as a means to increase the electron transport and reduce recombination between nanowire and electrolyte. Dye-sensitized solar cells (DSSCs) were prepared, for the first time, from arrays of urchin-like ZnO nanowire building blocks covered with a thin layer of anatase TiO2 by atomic layer deposition (ALD). An increase in the cell open-circuit voltage (VOC) and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
39
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(40 citation statements)
references
References 38 publications
(42 reference statements)
1
39
0
Order By: Relevance
“…Additionally, thanks to their inherent SERS activity [14], semiconductors have been used to fabricate metal/semiconductor hybrid nanostructures that exhibit both electromagnetic enhancement and charge-transfer effects [12]. Furthermore, these highly-efficient SERS hybrids present additional properties that make them attractive for applications such as photocatalysis [15], water splitting [16], and solar energy conversion [17]. As a semiconductor material with a wide direct bandgap (3.37 eV), biocompatibility [18], and promising optoelectronic properties [19,20], ZnO has been employed for the construction of highsurface-area SERS substrates with a wide range of tunable morphologies [21].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, thanks to their inherent SERS activity [14], semiconductors have been used to fabricate metal/semiconductor hybrid nanostructures that exhibit both electromagnetic enhancement and charge-transfer effects [12]. Furthermore, these highly-efficient SERS hybrids present additional properties that make them attractive for applications such as photocatalysis [15], water splitting [16], and solar energy conversion [17]. As a semiconductor material with a wide direct bandgap (3.37 eV), biocompatibility [18], and promising optoelectronic properties [19,20], ZnO has been employed for the construction of highsurface-area SERS substrates with a wide range of tunable morphologies [21].…”
Section: Introductionmentioning
confidence: 99%
“…Besides, Kretzschmar et al observed that the electron lifetime in photoanode films fabricated with NRs was 2 times longer compared to that with nanoparticles [21]. Apart from efficient electron transport, 1-D nanostructures with tunable lengths ranging from hundreds of nanometers to micrometers are also promising light-scattering centers with enhanced optical propagation distance within the films and improved light collection efficiencies [22,23,24]. Nevertheless, excessive loss of accessible surface area and thus insufficient dye loading of these ZnO nanostructures limits their attainable photovoltaic efficiency to a relatively low level, making them less competitive in current DSCs embodiments.…”
Section: Introductionmentioning
confidence: 99%
“…[ 113 ] A prototype is presented in Figure 7C, sea urchin‐inspired arrays of ZnO nanowire photoanode building blocks with a core‐shell 3D structure were covered with a thin layer TiO 2 . [ 114 ] In this design, an increased open‐circuit voltage and an improved conversion efficiency were observed that compared to other ZnO nanomaterial‐based dye‐sensitized solar cells. Using this, urchin‐like building blocks can improve the light‐ scattering and provide a higher surface area with a great control of the nanowire dimensions to increase the dye loading and reduce the electron collection path.…”
Section: Biological Materials and Bioinspired Design For Energy Harvesting Devicesmentioning
confidence: 96%
“…Reproduced with permission. [ 114 ] Copyright 2017, Elsevier Ltd. D) Biochemistry inspired solar cells. Left: working principle of a typical dye‐sensitized solar cell.…”
Section: Biological Materials and Bioinspired Design For Energy Harvesting Devicesmentioning
confidence: 99%